PENGARUH PROGRAM PENDIDIKAN PELATIHAN TERHADAP KINERJA PEGAWAI DI RUMAH SAKIT UMUM DAERAH NGANJUK - Yuliana Yuliana (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
This study aims to: 1 .Whether the education and training together influential significantly of the performance of employees at RSUD Nganjuk ? Research to be performed is ex post facto capital with the quantitative approach. Data collection method through kuisioner and documentation.The testing of hypotheses done by using regression analysis simple. This research result indicates that education and training ( X ) influential positive and significant against the employee performance ( Y ) .The analysis by the use of regression simple obtained the price of the regression coefficient worth 0,870 and price of the coefficients of 0,555 determination .After conducted t test obtained price t count as much as 6,788 and t table on significance level of 5 percent of 2,026 .This shows that tcount larger than ttable , which means the influence of education and training to the employee performance is significant .Thus can be inferred that education and training ( training ) influential positive and significant against the employee performance RSUD Nganjuk .It was because the education and training is one effort in the development of human resources for an organization , but performance improvement officer at each organization own have a percentage , likewise to employees RSUD Nganjuk.